2018
DOI: 10.3164/jcbn.17-62
|View full text |Cite
|
Sign up to set email alerts
|

How is edaravone effective against acute ischemic stroke and amyotrophic lateral sclerosis?

Abstract: Edaravone is a low-molecular-weight antioxidant drug targeting peroxyl radicals among many types of reactive oxygen species. Because of its amphiphilicity, it scavenges both lipid- and water-soluble peroxyl radicals by donating an electron to the radical. Thus, it inhibits the oxidation of lipids by scavenging chain-initiating water-soluble peroxyl radicals and chain-carrying lipid peroxyl radicals. In 2001, it was approved in Japan as a drug to treat acute-phase cerebral infarction, and then in 2015 it was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 106 publications
5
129
0
5
Order By: Relevance
“…Mean ± SEM, n = 4, ANOVA, Bonferroni test, *p < 0.05 compared to the control group; # p < 0.05 compared to the kainate-treated group in kainate-induced epilepsy models in rats [24,54]. All these preclinical data support the BBB protective effects of edaravone which may contribute to its efficacy in the clinical treatment of acute stroke and amyotrophic lateral sclerosis [17].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Mean ± SEM, n = 4, ANOVA, Bonferroni test, *p < 0.05 compared to the control group; # p < 0.05 compared to the kainate-treated group in kainate-induced epilepsy models in rats [24,54]. All these preclinical data support the BBB protective effects of edaravone which may contribute to its efficacy in the clinical treatment of acute stroke and amyotrophic lateral sclerosis [17].…”
Section: Discussionmentioning
confidence: 53%
“…The importance of the BBB as a therapeutic target is increasingly recognized and several anti-inflammatory or antioxidant drugs and novel molecules were identified as BBB protective on culture models [25] and introduced in the therapy of disease like stroke, amyotrophic lateral sclerosis and epilepsy [15][16][17]. We demonstrated that simvastatin protected brain endothelial cells in the Fig.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The σ S -response high-activity cell subpopulation may be considered a novel therapeutic target for potential inhibition of cipro-induced mutagenesis to antibiotic cross resistance. We show that the drug edaravone, an ROS scavenger indicated for human use in ALS in the U.S. and cerebral infarction in Japan (Miyaji et al, 2015; Watanabe et al, 2018), inhibits cipro induction of mutagenesis but not its antibiotic (killing) activity. Edaravone, at concentrations seen in new formulations (100μM) (Corporation, 2014; Li et al, 2012; Parikh et al, 2016), inhibited the appearance of σ S -high cells (Figure 3C), accumulation of σ S -fusion protein (Figure S3F), appearance of ROS-high cells (Figure 3D), and most (82% ± 1% of) RifR mutagenesis (Figure 3E).…”
Section: Resultsmentioning
confidence: 93%